Hypolimnetic Nutrient Subsidies to Surface Waters of a Large Lake: A Coupled Hydrodynamic Modelling and Nitrogen Isotope Field Assessment - Simon D. Stewart; David P. Hamilton; W. Troy Baisden; Piet Verburg; Kohji Muraoka; Derek C. Roberts; Brendan J. Hicks; Ian C. Duggan; Nico Donovan-Pereira (Ecosystems, 2025)
Upwelling of hypolimnetic water in lakes is important for littoral food webs as it enhances production through nutrient subsidies to surface waters. The aim of this study was to understand the role of hypolimnetic upwelling on littoral nutrient supply and diet of a freshwater unionid mussel, kākahi ( Echyridella menziesii) in an oligotrophic lake using stable isotopes (δ 15 N) as a tracer of hypolimnetic nitrogen. Upwelling events can be highly variable spatially and temporally, so to complement observations, this study used a three-dimensional hydrodynamic model (AEM3D) to simulate the transport of water from upwelling events and understand their potential impacts on kākahi. The study was conducted over an annual cycle in a large (area 620 km 2 , average depth ~ 94 m), monomictic, oligotrophic New Zealand lake. The hydrodynamic model simulations showed a strong spatial gradient. Upwelling was strongest along north-facing areas of the western shoreline owing to the prevailing south-westerly winds. The spatio-temporal distribution of nitrate-δ 15 N within the littoral zone was positively related to the rate of simulated upwelling, indicating inputs of 15 N-enriched hypolimnetic water. Kākahi δ 15 N values were positively related to upwelling averaged over an annual period, demonstrating that upwelling hotspots are ecologically meaningful. Interestingly, littoral particulate organic matter δ 15 N showed no pattern with upwelling but were homogeneous in distribution, consistent with rapid flushing with offshore water. These findings suggest that benthic littoral habitats act as hotspots for nutrient subsidies to surface waters, and that the signature of 15 N is retained over periods far longer than the duration of the upwelling by cycling within benthic primary producers and consumers.

Ultraviolet absorbents and industrial antioxidants in seabirds, mammals, and fish from the Canadian Arctic - Ingrid-Alejandra Granados-Galvan; Jennifer F. Provencher; Mark L. Mallory; Amila De Silva; Derek C.G. Muir; Jane L. Kirk; Xiaowa Wang; Robert J. Letcher; Lisa L. Loseto; Bonnie M. Hamilton; Zhe Lu (Science of The Total Environment, 2024)

Lateglacial and Early Holocene palaeoenvironmental change and human activity at Killerby Quarry, North Yorkshire, UK - Samuel M Hudson; Clive Waddington; Ben Pears; Natalie Ellis; Luke Parker; Derek Hamilton; Inger Greve Alsos; Paul Hughes; Antony Brown (Journal of Quaternary Science, 2023)
The hunter‐gatherers that entered the British peninsula after ice‐retreat were exploiting a dynamic, rapidly changing environment. Records of vegetation change and human occupation during the Lateglacial to Early Holocene in northern Britain are more commonly found at upland and cave sites. However, recent research highlights many areas of the Swale–Ure Washlands that preserve extensive environmental sequences in low‐lying ice‐wastage basins, channels and depressions. The Lateglacial–Early Holocene environment of Killerby Quarry, North Yorkshire, is investigated here using a multi‐proxy approach of sedimentary ancient DNA ( seda DNA), pollen, sedimentological (geochemistry and portable optically stimulated luminescence), and rare and well‐preserved archaeology (Lavvu structures and lithics). Results show that the wetland basins and kettleholes were small lakes or ponds in the Lateglacial surrounded by sedge‐fen and birch woodland. A gradual (centennial scale) succession to reed‐swamp and then marsh is seen by the Early Holocene. This environment formed the resource‐scape for hunter‐gatherer transitory settlement in both the Lateglacial (Late Upper Palaeolithic) and Holocene (Early Mesolithic), attracted by the rich communities of pond‐related flora and fauna as well as easy strategic landscape access by way of the River Swale, an arterial route through the landscape connecting the North Sea Basin with the Pennine uplands via the palaeolakes around Killerby.

The radiocarbon chronology and temporality of the megalithic cemetery of Los Millares (Almería, Spain) - Gonzalo Aranda Jiménez; Marta Díaz-Zorita Bonilla; Derek Hamilton; Lara Milesi; Margarita Sánchez Romero (Archaeological and Anthropological Sciences, 2020)

Western Juniper Management: Assessing Strategies for Improving Greater Sage-grouse Habitat and Rangeland Productivity - Shahla Farzan; Derek J. N. Young; Allison G. Dedrick; Matthew Hamilton; Erik C. Porse; Peter S. Coates; Gabriel Sampson (Environmental Management, 2015)

Karst geomorphology and hydrogeology of the bear rock formation — a remarkable dolostone and gypsum megabreccia in the continuous permafrost zone of northwest Territories, Canada - Jim Hamilton; Derek Ford (Carbonates and Evaporites, 2002)